Perceived value of the quality and sustainability of entrepreneurships proposed by Generation Z in the tourism sector in Salitre, 2024 - Huerta Cruz , Shirley Yadira; Segovia Velásquez , Elian Enrique; Vásquez Mendoza, Génesis Geraldine; Murillo Suárez, Andrés (Scripta Mundi, 2025)
This research is based on the growing importance of sustainability and quality in the tourism sector, as well as the role of Generation Z as a driver of innovation and local development. The study aimed to analyze the perceived quality and sustainability of tourism entrepreneurships proposed by Generation Z in the tourism sector of the Salitre canton in 2024. A quantitative approach was applied, utilizing a non-experimental cross-sectional design. A survey with 20 Likert-scale questions was administered to a sample of 80 entrepreneurs in the sector. The results indicated a predominantly favorable perception about the quality of the entrepreneurships; however, opinions about sustainability were divided. Deficiencies were identified in infrastructure, technological adoption, financial and commercial guidance, as well as a limited availability of resources for business development. Furthermore, the absence of strategic alliances and sustainable practices with community impact were observed. In response, the study recommends implementing continuous training strategies, strengthening collaboration networks, improving infrastructure, promoting community awareness, and incorporating a monitoring and evaluation system. The findings of this study provide key insights for the design of policies and programs that promote sustainability and competitiveness of tourism entrepreneurships in Salitre, contributing to job creation and the region’s economic and social growth.
Keywords: Quality; Entrepreneurship; Generation Z; Sustainability